Internalization of Multicultural Values in Fiqh Learning at Muhammadiyah Boarding School Al-Mujahidin Gunungkidul - Abdul Azis; Mastur; Hafizatur Rahmi; Muhammad Arif Bin Che Hasim; Eko Tuanto; Abd Rachman Mildan; Muhammad Auwalul Muttaqin; Fitra Asysyifa (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study aims to analyze the process and outcomes of internalizing multicultural values in fiqh learning to develop students’ humanistic character at Muhammadiyah Boarding School Al-Mujahidin Gunungkidul. This research employed a qualitative field research design. The informants consisted of three fiqh teachers and 91 students from grades VII–IX. Data were collected through classroom observations, semi-structured interviews, and questionnaires. Data triangulation was conducted using source triangulation (teachers and students) and technique triangulation (observation, interviews, and questionnaires), with the unit of analysis focusing on learning processes, instructional strategies, and students’ behavioral responses. The findings indicate that the internalization of multicultural values was implemented through comparative madhhab approaches, contextual learning, group discussions, and project-based activities. Quantitative questionnaires show that all indicators achieved high mean scores ranging from 4.0 to 4.5 on a 5-point Likert scale. The highest scores were found in respect for differences (4.4) and the application of tolerance and justice in dormitory life (4.3). These results demonstrate that fiqh learning has effectively fostered dominant patterns of tolerance, empathy, cooperation, and fairness among students. The study concludes that integrating multicultural values into fiqh learning contributes significantly to the formation of students’ humanistic character and supports the development of moderate and inclusive Islamic education within boarding school contexts.